Assessment of upper limb abnormalities using the Kinect: Reliability, validity and detection accuracy in people living with acquired brain injury. (2nd December 2021) - Pashley, Gabrielle L.; Kahn, Michelle B.; Williams, Gavin; Mentiplay, Benjamin F.; Banky, Megan; Clark, Ross A.
Abstract: Upper limb kinematic abnormalities are prevalent in people with acquired brain injury (ABI). We examined if the Microsoft Kinect for Xbox One (Kinect) reliably (test–retest) and validly (concurrent) quantifies upper limb kinematics, and accurately classifies abnormalities (sensitivity/specificity), in an ABI cohort when compared to three-dimensional motion analysis (3DMA) and a subjective rating scale. We compared 42 adults with ABI to 36 healthy control (HC) participants. Walking trials were recorded by 3DMA and Kinect at self-selected (SSWS) and fast (FWS) walking speeds. When classifying abnormalities for 3DMA and Kinect, a 95% reference range (based on HC data) was calculated using the Kinematic Deviation Score worst axis (KDSw); values outside of this range were classified abnormal. Scores ≥ 2 in the subjective rating scale, based on International Classification of Functioning, Disability and Health Framework's Qualifiers Scale, were considered abnormal. Test-retest reliability and concurrent validity were determined using intra-class correlation coefficient (Absolute ICC2, 1 ) and Pearson's or Spearman's correlation respectively. Fisher's Exact Test was conducted to determine sensitivity and specificity between each combination of the two methods. Strong test–retest reliability was observed for 3DMA (median(IQR) ICC:0.86(0.85–0.90)). Kinect showed overall strong SSWS test–retest reliability (ICC:0.87(0.84–0.91)) and moderate FWS test–retest reliability (ICC:0.61(0.56–0.65)). Concurrent validity between 3DMA and Kinect was overall moderate. Sensitivity and specificity between 3DMA, Kinect and subjective scores were overall modest. Our results suggest caution should be used if implementing Kinect as its validity is modest against criterion-reference 3DMA; however, given its reliability and similar sensitivity/specificity to 3DMA further responsiveness research is warranted.